A recent advances in antimicrobial activity of green synthesized selenium nanoparticle - Durgadevi Ravi; Bhuvaneshwari Gunasekar; Vishwanathan Kaliyaperumal; Shyamaladevi Babu (OpenNano)
Green technologies have gained prominence, particularly in the environmentally friendly synthesis of compounds, with Selenium nanoparticles (SeNPs) emerging as a key area of interest due to their potential in drug development. The sustainable production of SeNPs using microorganisms and plants enhances their physical, chemical, and biological properties, improving their catalytic efficiency. Recent advancements in nanotechnology, especially in medicine and antimicrobial research, highlight the growing significance of green synthesis methods. These eco-conscious approaches aim to preserve natural resources while promoting sustainable nanoparticle production techniques. This review focuses on SeNPs' antimicrobial action as well as the factors that influence their green production, such as pH, temperature, and precursor concentration, all of which affect their morphology, size, and stability. SeNPs' antimicrobial activity against a diverse range of bacteria, fungi, and viruses is extensively tested, with a focus on their capacity to battle drug-resistant infections and biofilms. The mechanisms of SeNPs' antimicrobial effect are investigated, including membrane disruption, reactive oxygen species (ROS) production, and interactions with cellular components. Furthermore, their antiviral characteristics and ability to alter immune responses highlight their medicinal applications. SeNPs represent a significant advancement in green nanotechnology, offering sustainable solutions to pressing biomedical challenges, particularly in the fight against drug-resistant pathogens.